Improving Outpatient’s Quality of Life Through Patient Adherence of Antihypertensive Therapy Using “Mobile Phone (SMS) and Brief Counseling‑5A” in Polyclinic of Internal Medicine at PKU Muhammadiyah Bantul Hospital, Yogyakarta - Ginanjar Z. Saputri; Akrom Akrom; Endang Darmawan (Indonesian Journal of Clinical Pharmacy, 2017)
The Health-Related Quality of Life (HRQoL) is one of the important psycho-social characteristics that can affect patient’s ability to manage therapy. Poor of knowledge of hypertension and the changing lifestyle can affect the quality of life of patients. One of the pharmacist’s interventions in hypertension management is to conduct counseling. Motivational counseling helps health service to assess patient’s understanding and patient’s readiness to change patient’s behavior. Some motivational counseling methods still need to be developed. Therefore, this study aims to find the influence of the “brief counseling-5A” and “motivational SMS” by a pharmacist on the quality of life and blood pressure control in hypertension patients in the internal disease polyclinic, PKU Muhammadiyah Bantul Hospital, Yogyakarta. The study has been done by using the quasi-experimental method with prospective data collection during the period of January until April 2013. Sixty patients have met inclusion criteria and were divided into two groups. Thirty patients (50%) received “brief counseling-5A” and “motivational SMS” as intervention group and the other thirty patients (50%) received usual care as a control group. The data collection was done by interviewing patients. Medication adherence and QoL were assessed by using Morisky Medication Adherence Scale (MMAS) and SF-36. The values of blood pressure are taken from patient’s medical records. Patient’s quality of life showed a good improvement during post study. It is shown in 8 different domains including pain, fatigue, physical function, emotional function, social function, role physical, mental health, and general health. In intervention group, physical function, emotional function, and pain showed highly significant improvement (p<0.05). Systolic and diastolic blood pressure in the intervention group decreased significantly (p<0.05) (systolic p=0.001 and diastolic p=0.018) in the post study. From this study, it is concluded that the “brief counseling-5A by pharmacist” and “motivational SMS” had a positive impact on patient’s QoL and patient’s blood pressure, hence, the therapy outcome has been achieved.Keywords: Adherence, blood pressure, brief counseling, hypertension, quality of life, SMS Peningkatan Kualitas Hidup (QoL) Melalui Kepatuhan Terapi Antihipertensi dengan Mobile Phone Text Messaging (SMS) dan Brief Counseling-5A pada Pasien Rawat Jalan Poliklinik Penyakit DalamRumah Sakit PKU Muhammadiyah Bantul, YogyakartaAbstrakHubungan kesehatan dan kualitas hidup (Health Related Quality of Life) merupakan salah satu karakter psiko‑sosial penting yang dapat memengaruhi kemampuan pasien dalam penatalaksanaan terapi. Kurangnya pengetahuan mengenai hipertensi dan perubahan gaya hidup dapat memengaruhi kualitas hidup pasien. Salah satu intervensi farmasis dalam penatalaksanaan hipertensi adalah konseling. Konseling motivasional membantu pelayanan kesehatan untuk menggali pemahaman pasien serta kesiapan pasien untuk berubah. Tujuan penelitian ini adalah untuk mengetahui pengaruh pemberian brief counseling-5A disertai SMS motivasi oleh farmasis terhadap kualitas hidup dan pengontrolan tekanan darah pasien hipertensi di poliklinik penyakit dalam RS PKU Muhammadiyah Bantul, Yogyakarta. Penelitian dilakukan secara kuasi eksperimental dengan pengambilan data secara prospektif selama periode Januari hingga April 2013. Sejumlah 60 subjek yang memenuhi kriteria inklusi dibagi menjadi dua kelompok yaitu 30 pasien (50%) mendapatkan brief counseling-5A serta SMS motivasional (kelompok perlakuan) dan 30 pasien (50%) mendapatkan pelayanan kefarmasian konvensional (usual care) sebagai kontrol. Pengumpulan data dilakukan dengan melakukan wawancara dan pengisian kuesioner kepatuhan Morisky Medication Adherence Scale (MMAS), dan kuesioner kualitas hidup SF-36. Nilai tekanan darah diambil dari catatan medis. Kualitas hidup pasien hipertensi menunjukkan peningkatan rerata pada kunjungan kedua (post) di semua domain baik nyeri, fatigue, fungsi fisik, fungsi emosi, fungsi sosial, keadaan fisik, keadaan emosi (status mental), dan keadaan umum (kesehatan umum). Perubahan yang bermakna (p<0,05) terjadi pada domain fungsi fisik (FF), fungsi emosi (FE) dan nyeri. Terjadi penurunan tekanan darah sistolik (p=0,001) dan diastolik (p=0,018) pada kelompok perlakuan sementara pada kelompok kontrol tidak terjadi penurunan tekanan darah sistolik (p=0,730) dan diastolik (p=0,786). Berdasarkan hasil penelitian ini, dapat disimpulkan bahwa pemberian brief counseling-5A serta SMS motivasional oleh farmasis pada pasien hipertensi memberikan pengaruh positif terhadap kualitas hidup pasien dan tekanan darah sehingga tujuan terapi antihipertensi tercapai.Kata kunci: Brief counseling, hipertensi, kepatuhan, kualitas hidup, SMS, tekanan darah